Elective hepatic resection is feasible and safe in a regional centre. Issue 3 (14th November 2016) - Gray, Andrew D.; Petrou, George; Rastogi, Pratik; Begbie, Stephen
Abstract : Background: Hepatic resectional surgery remains a highly specialized area of general surgery usually reserved for completion at tertiary metropolitan referral centres. Port Macquarie, on the Mid North Coast of New South Wales, is the only regionally based hospital offering surgery of this nature in mainland Australia. The purpose of this study is to review the data for patients undergoing hepatic resectional surgery in this non‐metropolitan centre in order to illustrate that these operations can be carried out safely in a regional setting with comparable results to tertiary‐level centres. Methods: A retrospective review of consecutive patients undergoing elective hepatic resections at Port Macquarie from February 2008 to 31 October 2015 was completed. Pre‐morbid patient clinical and demographic factors, histopathological details, post‐operative complications, survival and mortality data were all noted. Results: A total of 66 consecutive elective liver resections were performed during the study period. Metastatic colorectal cancer was the most commonly observed pathology ( n = 33, 50.0%). The 90‐day mortality was 4.5% ( n = 3) whilst 17 patients ( n = 17, 25.8%) experienced major complications (Clavien–Dindo grade 3 or 4). The median overall survival following hepatectomy for colorectal metastases was 48 months (95% confidence interval 37–59 months). Conclusion: Our study shows excellent morbidity, mortality and survival for hepatic resectional surgery performed in a regional centre and is comparable data to major metropolitan centres. Our study confirms that major hepatic resectional surgery in this setting is safe and effective.